2015
DOI: 10.1080/10826076.2015.1020164
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metabolomic Approach for Evaluating Antioxidant Capacity and Its Application

Abstract: Metabolomics is frequently used in the analysis of the dynamic changes within small molecules in response to the disturbance in an organism. It has been extensively used in various fields involving human diseases. To better evaluate the antioxidant capacity, cells subjected to oxidative stress were cultured, and the intracellular metabolites were prepared using HSDE (high-speed shear dispersing emulsifier)-assisted extraction. The metabolites were then analyzed under optimized chromatographic conditions. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…For example, conventional extraction of anthocyanins is typically conducted at temperatures ranging from 20 to 50°C (Jackman et al, 1987), and temperatures higher than 70°C cause rapid anthocyanin degradation (Havlikova and Mikova, 1985). Liu et al (2015) confirmed that HSDE-assisted extraction could promote the release of intracellular metabolites, and the production was clearly enhanced when the shearing time increased from 0 to 3 min.…”
Section: Discussionmentioning
confidence: 79%
“…For example, conventional extraction of anthocyanins is typically conducted at temperatures ranging from 20 to 50°C (Jackman et al, 1987), and temperatures higher than 70°C cause rapid anthocyanin degradation (Havlikova and Mikova, 1985). Liu et al (2015) confirmed that HSDE-assisted extraction could promote the release of intracellular metabolites, and the production was clearly enhanced when the shearing time increased from 0 to 3 min.…”
Section: Discussionmentioning
confidence: 79%